A comparison of teacher’s involvement in curriculum development in developing and developed countries: a case study of Namibia - Matiki, DesRee Sabata; Chibambo, Mackenzie Ishmael; Divala, Joseph Jinja (Frontiers in Education, 2023)
Curriculum development is an on-going process which involves different stakeholders such as teachers, parents, curriculum specialists, academic institutions and the general public. The involvement of all these stakeholders is essential for the success of any curriculum. This study sought to determine how teachers are involved in the curriculum development processes in Namibia. It did this by examining related literature from selected developing and developed countries on teacher involvement in the curriculum development processes. It further deployed a qualitative research approach which had a sample size of 11 secondary school teachers and six NIED officials who were interviewed. The empirical data alongside the reviewed literature, and the theoretical framework were thematically analysed. The findings revealed that secondary school teachers in Namibia did not meaningfully participate during the key stages of the curriculum development processes. These findings further affirmed the assumptions that teacher’s voices are mostly discounted during curriculum development processes despite the centrality of their roles and functions. The study further established that Namibia, like many African countries, use the top-down approaches when developing their curricula unlike developed countries such as Australia, Finland and Singapore.